CERAMIC BASINS FROM THE “KILNS OF VINGONE” IN SCANDICCI (FLORENCE/ ITALY): Aegean shapes in pottery production in the area of Roman Florentia - Fabbri, Fabiana (Rei Cretariae Romanae Fautorum Acta, 2024)
This article is a partial preview of the book about to be published by the Soprintendenza ai Beni Archeologici della Toscana by G. Capecchi, G. de Marinis, A. Patera and E. J. Shepherd on the ceramic production of the Vingone kilns situated in the borough of Scandicci, south-west of the city of Florence, in Tuscany.